Gender differences in pain and healthcare utilization for adult sickle cell patients: The PiSCES Project - McClish, Donna K; Levenson, James L; Penberthy, Lynne T; Roseff, Susan D; Bovbjerg, Viktor E; Roberts, John D; Aisiku, Imoigele P; Smith, Wally R (Journal of women's health (Larchmont, N.Y. 2002), 2006)
Many studies have found gender differences in frequency and intensity of pain. Women often report lower pain thresholds, higher pain ratings, and lower tolerance for pain. People with sickle cell disease (SCD) experience both chronic and acute pain throughout life. To compare adult men and women with SCD in terms of reported pain, crises, healthcare utilization, and opioid usage. Two hundred twenty-six adults with SCD in Virginia were enrolled in a prospective cohort study of pain and completed daily diaries for 1-6 months. Subjects reported for the previous day their maximum SCD-related pain, distress, and interference (0-9 scale), whether they were in a sickle cell crisis, had unplanned utilization (clinic, emergency room, or hospitalization), or used opioids. Episodes of pain, crisis, or utilization were defined as consecutive days of such. Men and women were compared, using analysis of covariance (ANCOVA), controlling for age, SCD genotype, depression, and education. There were no significant differences between men and women in the percentage of days subjects experienced pain (men 58.6% vs. women 56.5%) or the number of pain episodes/6 months (7.7 vs. 9.6). Mean pain scores were comparable, when subjects were in crisis (5.5 vs. 5.6) or not (2.5 vs. 2.2). Distress and interference results were similar. Men with the SS genotype reported a higher percentage of days with crisis(18.5% vs. 11.6%) and utilization (5.1% vs. 2.7%) than women with the SS genotype. Contrary to many studies of pain, particularly chronic pain, men and women with SCD reported generally similar pain experiences.